COVID-19, an opportunity to reevaluate the correlation between long-term effects of anthropogenic pollutants on viral epidemic/pandemic events and prevalence. (July 2020) - Tsatsakis, Aristidis; Petrakis, Demetrious; Nikolouzakis, Taxiarchis Konstantinos; Docea, Anca Oana; Calina, Daniela; Vinceti, Marco; Goumenou, Marina; Kostoff, Ronald N.; Mamoulakis, Charalampos; Aschner, Michael; Hernández, Antonio F.
Abstract: Occupational, residential, dietary and environmental exposures to mixtures of synthetic anthropogenic chemicals after World War II have a strong relationship with the increase of chronic diseases, health cost and environmental pollution. The link between environment and immunity is particularly intriguing as it is known that chemicals and drugs can cause immunotoxicity (e.g., allergies and autoimmune diseases). In this review, we emphasize the relationship between long-term exposure to xenobiotic mixtures and immune deficiency inherent to chronic diseases and epidemics/pandemics. We also address the immunotoxicologic risk of vulnerable groups, taking into account biochemical and biophysical properties of SARS-CoV-2 and its immunopathological implications. We particularly underline the common mechanisms by which xenobiotics and SARS-CoV-2 act at the cellular and molecular level. We discuss how long-term exposure to thousand chemicals in mixtures, mostly fossil fuel derivatives, exposure toparticle matters, metals, ultraviolet (UV)–B radiation, ionizing radiation and lifestyle contribute to immunodeficiency observed in the contemporary pandemic, such as COVID-19, and thus threaten global public health, human prosperity and achievements, and global economy. Finally, we propose metrics which are needed to address the diverse health effects of anthropogenic COVID-19 crisis at present and those required to prevent similar future pandemics. Graphical abstract: Image 1 Highlights: Developmental exposure to environmental factors can disrupt the immune system. Long-term low-dose exposure to chemical mixtures is linked to imunodeficiency Immunodeficiency contributes to chronic diseases and the current Covid-19 pandemics. Environmental chemicals and microorganisms share similar molecular pathomechanisms (AhR pathway). Understanding the underlying pathomechanisms helps to improve public health.